QUANTUM COMPUTING AND LEGAL READINESS FOR E-GOVERNMENT SERVICES - Abdikhakimov, Islombek (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Quantum computing promises unprecedented processing power that could revolutionize e-government services. However, realizing this potential requires updating legal frameworks on data privacy, cybersecurity, intellectual property, and procurement. This paper provides an overview of quantum computing and its applications to e-government. It analyzes gaps in current laws and regulations, arguing for benchmarks towards legal readiness. Recommendations focus on data protection standards, liability rules, transparency policies, interagency collaboration, and public-private partnerships. With timely legislation and strategic planning, governments can harness quantum computing for more secure, efficient, and equitable public services.